Private: 'Human trafficking, sex trade' is Criminology alumni topic Sept. 19 - Uribes, Tom::::::::: (2013)
Fresno State's Criminology Alumni Chapter presents 'Human Trafficking and the Sex Trade: from Slavery to Freedom, a Collaborative Response,'